2013
DOI: 10.1042/bj20130788
|View full text |Cite
|
Sign up to set email alerts
|

Dual lipidation of the brain-specific Cdc42 isoform regulates its functional properties

Abstract: Cdc42 (cell division cycle 42) is a member of the Rho GTPase family which regulates a variety of cellular activities by controlling actin cytoskeleton and gene expression. Cdc42 is expressed in the form of two splice variants. The canonical Cdc42 isoform is prenylated (Cdc42-prenyl), whereas the brainspecific isoform can be palmitoylated (Cdc42-palm). In the present study we have demonstrated palmitoylation of endogenous Cdc42 in rodent and human brains and identified Cys(188) and Cys(189) as acylation sites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(99 citation statements)
references
References 58 publications
3
96
0
Order By: Relevance
“…Cdc42Palm is palmitoylated, whereas the canonical form is not (Nishimura et al, 2013; Kang et al, 2008). Wirth et al (2013) reported that the expression level of Cdc42Palm in the hippocampus was approximately 2-fold higher than that of isoform 1. We specifically examined the involvement of Cdc42Palm in axonal growth.…”
Section: Resultsmentioning
confidence: 99%
“…Cdc42Palm is palmitoylated, whereas the canonical form is not (Nishimura et al, 2013; Kang et al, 2008). Wirth et al (2013) reported that the expression level of Cdc42Palm in the hippocampus was approximately 2-fold higher than that of isoform 1. We specifically examined the involvement of Cdc42Palm in axonal growth.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the ‘upstream’ proteins that regulate PAK/LIMK1 activity in spines are not known, but it is striking that palmitoylated forms of both Rac and Cdc42, small GTPases that are well known regulators of LIMK1 signaling, are detected in neurons (Kang et al, 2008, Wirth et al, 2013). Moreover, a palmitoylated form of Cdc42 is dominantly expressed in hippocampus (compared to the prenylated form, which is dominant in most other tissues), is preferentially targeted to dendritic spines, and is important for the control of spine morphology (Wirth et al, 2013, Kang et al, 2008). These findings raise the possibility that palmitoylation controls the spine localization and activity of multiple elements of the Rac/Cdc42-PAK-LIMK1 signaling module (Figure 2).…”
Section: Regulation Of Neuronal Cytoskeletal Dynamics By Palmitoylatementioning
confidence: 99%
“…Cdc42 alternative splicing has long remained neglected until recent works showed striking differences in the ability of the two isoforms to induce filopodia (Wirth et al, 2013). The ubiquitous Cdc42 isoform is prenylated, whereas the alternative isoform is brain specific and can be palmitoylated thanks to the cysteine doublet of the CAAx box.…”
Section: Diversification Of the Rho Family In Metazoamentioning
confidence: 99%